Transdiagnostic symptom networks in relation to mental health service use in community youth - Imperiale, Marina N.; Lieb, Roselind; Calkins, Monica E.; Meinlschmidt, Gunther (Clinical psychology and psychotherapy, 2023)
Objective The objective of this study is to scrutinize whether psychopathology symptom networks differ between those with and without lifetime: treatment seeking, treatment and treatment of longer duration. Methods We created non‐exclusive groups of subjects with versus without lifetime treatment seeking, treatment and treatment of mid‐long‐term duration. We estimated Ising models and carried out network comparison tests (NCTs) to compare (a) overall connectivity and (b) network structure. Furthermore, we examined node strength. We used propensity score matching (PSM) to minimize potential confounding by indication for service use. Results Based on data from 9,172 participants, there were no statistically significant differences in overall connectivity and network structure in those with versus without lifetime: treatment seeking (p = .75 and p = .82, respectively), treatment (p = .63 and p = .49, respectively) and treatment of mid‐longterm duration (p = .15 and p = .62, respectively). Notably, comparing networks with versus without service use consistently revealed higher node strength in ‘obsessions’ and ‘aggression’ and lower node strength in ‘elevated mood’ in all networks with service use. Conclusions Findings suggest that after adjusting for potential confounding by indication for service use, there was no indication of an association in overall connectivity or network structure for lifetime treatment seeking, treatment and treatment of longer duration. However, selected structurally important symptoms differed consistently in all three comparisons. Our findings highlight the potential of network analysis methods to examine treatment mechanisms and outcomes. Specifically, more granular network characteristics on the node level may complement and enrich traditional outcomes in clinical research.